The Psychospiritual Meaning of Badal Haji in the Book of Al-Fiqh al-Islami wa Adillatuhu by Wahbah al-Zuhaili : Makna Psikospiritual Badal Haji dalam Kitab Al-Fiqh al-Islami wa Adillatuhu Karya Wahbah al-Zuhaili - Muhammad Sholachuddin; Kurnia Muhajarah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
Badal Hajj is a ritual of worship representing Hajj on behalf of other people who are prevented from carrying it out because they are late or have died. Wahbah al - Zuhaili in his work Buku Al Fiqh wa Islami Adilatuhu explains various views from the four schools of thought regarding the meaning, requirements and legal basis of badal hajj. This research aims to find out the psychospiritual meaning of badal hajj based on the book written by al - Zuhaili. The results of this research show that badal hajj contains psychospiritual meaning for Muhaddil, apart from training responsibility for the person entrusted to it, badal hajj is also a means of increasing spirituality and strengthening faith. Meanwhile, for people who are being offered the Hajj, the presence of a badal brings calm and gratitude because their obligations have been fulfilled. This research proves that there is an integrated relationship between fiqh and psychospiritual knowledge in the practice of the Hajj pilgrimage.